Suspected COVID-19 flu-like syndrome in men who have sex with men and have been involved in casual sex - Carvalho,Herica Emilia Félix de (2020)
ABSTRACT Objective: To evaluate the presence of flu-like syndrome suggestive of COVID-19 in men who have sex with men (MSM) and engaged in casual sex during a period of social isolation. Method: National epidemiological survey, applied in April and May 2020, by adaptation of Respondent Drive Sampling. Results: 1,337 MSM participated in the survey, of which 514 (38.4%) had fever associated with another sign or symptom of flu-like syndrome. Social, demographic characteristics, sexual practices and activities during the period of social isolation were statistically associated with the presence of flu-like syndrome. There was a statistical difference (p < 0.001) in the average of partners between those who had signs and symptoms of flu-like syndrome (3.5) and those who did not (1.7). Conclusion: Evidence of signs and symptoms indicative of flu-like syndrome suggestive of COVID 19 in Brazilian MSM who were involved in casual sex during the period of social isolation.